2015
DOI: 10.1111/ina.12258
|View full text |Cite
|
Sign up to set email alerts
|

The MERMAID study: indoor and outdoor average pollutant concentrations in 10 low‐energy school buildings in France

Abstract: Indoor air quality was characterized in 10 recently built energy-efficient French schools during two periods of 4.5 days. Carbon dioxide time-resolved measurements during occupancy clearly highlight the key role of the ventilation rate (scheduled or occupancy indexed), especially in this type of building, which was tightly sealed and equipped with a dual-flow ventilation system to provide air refreshment. Volatile organic compounds (VOCs) and inorganic gases (ozone and NO2 ) were measured indoors and outdoors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
5
41
2
Order By: Relevance
“…The other aldehydes concentrations inside the classroom were measured using the reference ISO 16000-3 method based on DNPH derivatization from 24 February to 7 March 2015 (see Figure 4). Except formaldehyde, acetaldehyde was the main aldehyde detected, as was previously observed by previous studies in indoor air [4,11,39]. Its concentrations ranged between 2 and 5 µg m −3 , whereas the concentrations of the remaining aldehydes, i.e., hexanal, propanal, and benzaldehyde were lower than 1 µg m −3 .…”
Section: Monitoring Of Other Aldehydes In the Classroomsupporting
confidence: 82%
See 1 more Smart Citation
“…The other aldehydes concentrations inside the classroom were measured using the reference ISO 16000-3 method based on DNPH derivatization from 24 February to 7 March 2015 (see Figure 4). Except formaldehyde, acetaldehyde was the main aldehyde detected, as was previously observed by previous studies in indoor air [4,11,39]. Its concentrations ranged between 2 and 5 µg m −3 , whereas the concentrations of the remaining aldehydes, i.e., hexanal, propanal, and benzaldehyde were lower than 1 µg m −3 .…”
Section: Monitoring Of Other Aldehydes In the Classroomsupporting
confidence: 82%
“…Most of the studies required passive sampling on the DNPH tubes [3,4,[40][41][42] over a period of several days to a week, except Jarnstrom et al (2006) [43], who used active sampling using a 0.005 M sulfuric solution at 2-4 L/min, followed by a derivatization with acetyl-acetone and quantification by a spectrometric method. Our study appears to be the first one to report continuous formaldehyde monitoring in a low-energy building.…”
Section: Comparison With Previous Aldehydes Measurements Performed Inmentioning
confidence: 99%
“…Indoor exposure and time–activity patterns may introduce some bias, although this will most likely be nondifferential and thus would generally tend to attenuate the associations. Furthermore, several measurement studies conducted in different areas have demonstrated that indoor and outdoor NO 2 levels are strongly correlated ( R 2 = 0.7–0.9), pointing to indoor NO 2 concentrations being largely affected by outdoor sources (El-Hougeiri and El Fadel 2004; Verriele et al 2015; Wichmann et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Besides, using effective means to reduce indoor air pollution and improve air quality are important issues for building occupants and users in nonventilated places, like hospitals and laboratories (Brown et al, 2015;Lucas et al, 2016;Verriele et al, 2016;Bradman et al, 2017). Indoor air handling systems with HEPA filters control the ambient environmental conditions, including the temperature, humidity, air flow and air cleaning (Russell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%